Research site monitoring for compliance with ethics regulatory standards: review of experience from Uganda - Ochieng, Joseph; Ecuru, Julius; Nakwagala, Frederick; Kutyabami, Paul (BMC Medical Ethics, 2013)
On site monitoring of research is one of the most effective ways to ensure compliance during research conduct. However, it is least carried out primarily for two reasons: presumed high costs both in terms of human resources and finances; and the lack of a clear framework for undertaking site monitoring. In this paper we discuss a model for research site monitoring that may be cost effective and feasible in low resource settings. Methods: This was a retrospective review of research site monitoring reports covering a period of four years. Results: The monitoring was conducted by the Uganda National Council for Science and Technology, the National Drug Authority and the National HIV/AIDS Research and Ethics Committee over the period 2007 to 2010. The monitoring team was usually three members comprising of two experts in research ethics and an assistant. A total of 28 site monitoring visits covering 40 research projects were reviewed. 25% of the site monitoring reports revealed violation of the regulatory requirement for valid ethical approval. 36% of the site reports showed some instances of informed consent violation, 28% showed violation of the rights and welfare of research participants, 38% revealed that sites did not report SAEs to regulatory authorities and many sites lacked adequate GCP and GCLP. However, most of the sites monitored had adequate facilities to conduct the respective studies and good working practices. Conclusion: This model employed by the monitoring teams to evaluate research compliance is effective in auditing ethical practice. Compliance monitoring is feasible and affordable in a resource limited setting. Research protocol non compliance is still a major problem in Uganda, and there is need for a pro-active approach to this vice by all stake holders if ethical conduct of research is to be achieved.
Keywords: Research; Monitoring; Compliance; Ethics; Uganda